Improvement of Asymmetric Vestibulo-Ocular Reflex Responses Following Onset of Vestibular Neuritis Is Similar Across Canal Planes - Allum, John H. J.; Honegger, Flurin (Frontiers in Neurology, 2020)
Background: We examined whether, after onset of acute unilateral vestibular neuritis (aUVN), initial disease effects, subsequent peripheral recovery and central compensation cause similar changes in vestibular ocular reflex (VOR) gains in all 3 semi-circular canal planes. Methods: 20 patients, mean age 56.5 years, with pathological lateral canal video head impulse test (vHIT) VOR gains due to aUVN, were subsequently examined with vHIT in all 3 canal planes on average 4.3 and 36.7 days (“5 weeks”) after aUVN onset. Results: Lateral and anterior deficit side (DS) average gains equaled 0.41 at aUVN onset. Non-deficit, normal, side (NS) gains were 0.88 and 0.81, respectively. Mean posterior DS gain was similar at onset, 0.43, provided only gains lower than 0.6 (lower limit of healthy controls) were considered. NS posterior mean gain at onset (0.68) was less (p ≤ 0.0006) than lateral and anterior NS gains. After 5 weeks, DS lateral, anterior and posterior canal gains increased (p ≤ 0.05), on average, to 0.65, 0.59, and 0.58, respectively. NS gains increased to 0.91, 0.87, and 0.76 (p = 0.007), respectively. At 5 weeks deficit-lateral/normal-lateral canal plane gain asymmetries were significantly (p < 0.0008) reduced from 36.9 to 19.4%, deficit-anterior/normal-posterior asymmetry decreased from 28.6 to 18.1%, while deficit-posterior/normal-anterior asymmetry changed from 29.7 to 21.4%, all to circa 20%. Roll plane asymmetries decreased slightly over 5 weeks (28.6–18.1%) but pitch plane asymmetries remained significantly less (p = 0.001), not different from 0% regardless of initial DS posterior canal vHIT gain. Yaw plane asymmetry changes are identical to those of the lateral canals (36.7–19.4%). Conclusions: These results indicate that, at onset, aUVN of the superior vestibular nerve has a similar effect on lateral and anterior deficit DS VOR gains, and on posterior DS canal VOR gains if the inferior nerve was also affected at onset. The significant improvements to equal 5 week levels of DS gains and slightly greater posterior NS gain improvements, compared to lateral and anterior NS gains, yielding a common canal plane gain asymmetry of 20% at 5 weeks, suggest similar neural compensation mechanisms were active along VOR pathways. Unexpectantly, canal plane improvement was not replicated in pitch plane asymmetries.